Effects of early life factors on the health and quality of life of older adults. Issue 1 (26th July 2017) - Yilmaz, Fikriye; N. Tekin, Rukiye
Abstract : Background: Few studies on the effects of early life factors on the health and quality of life of adults have been conducted in Turkey. We aimed to investigate the effects of early life factors on the health and quality of life of older adults. Methods: We administered a questionnaire to 350 adults, aged 50–89 years, living in Cankaya, Ankara. The questionnaire covered sociodemographic characteristics, early life characteristics, health status, and the World Health Organization Quality of Life–Ageing scale. Data were analyzed using χ 2 tests, independent samples t ‐tests, one‐wayanova, and binary logistic regression analysis. Results: The analyses showed that the most important risk factors for chronic disease were being ≥65 years (odds ratio (OR) = 2.34), having a chronic health problem before 18 years of age (OR = 2.48), experiencing prolonged hospitalization or bed rest before 18 years of age (OR = 2.65), and experiencing parental unconcern during early life (OR = 2.13) ( P  < 0.05). In addition, having a high school education or less includes people who have primary or secondary or high school diploma (OR = 1.65), having lived in a village (OR = 1.65), having a low family economic status (OR = 2.40), and having experienced one negative event (OR = 1.41) or two or more negative events (OR = 1.39) during their early lives were identified as important risk factors for low quality of life ( P  < 0.05). Conclusion: Early life factors are among the important determinants of the health and quality of life of older adults in Turkey.